The co-evolution mechanism and stability analysis of service-oriented manufacturing enterprise system - Peipei Liang; Yanming Sun; Yali Pan (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: Service-oriented manufacturing (SOM) is a new worldwide trend in the manufacturing industry. An increasing number of enterprises have realized the advantages and importance of SOM. However, the co-evolution mechanism and the stability of service-oriented manufacturing enterprise systems have influences on the form and direction of evolution and decisions about how to determine the suitable scope of external investment. This paper aims to reveal the co-evolution mechanism and provide a scientific framework for the efficient operation of SOM enterprise system. Design/methodology: Based on a system's features and the logistic equation, our research builds a three-dimensional dynamic model with three state variables: response capability, profitability, and structural complexity. In addition, an analysis of a system's stability and state variables is conducted using the method of synergetics and, simultaneously, the threshold condition of co-evolution was determined and the evolution mechanism revealed. Finally, model validity is verified through the simulation of instance. Findings: By analyzing the dynamic model using Lyapounov stability analysis, the results show that responsiveness under the threshold condition will guide an enterprise system's evolution for a long period of time, and whether the SOM enterprise system is stable or not depends on the external investment level 0. When the investment level reaches the threshold condition, system will realize its development and then repeatedly change from one kind of structure to another for an extended period. If not, system will be unstable, although it will improve, the rise in responsiveness will not be obvious. Originality/value: Most of the related researches are over-reliant on qualitative description and has seldom been from the perspective of a complex system. This work is a supplement from evolution perspective to SOM related theory researches, and also an innovation in the context of complexity science methods applied in enterprise management field.
Keywords: 650; service-oriented manufacturing; complex system; dynamic model co-evolution; stability